Peran Muhammadiyah Mengatasi Khurafat dalam Masyarakat Islam Kecamatan Pegajahan (Studi Kasus: Desa Sukasari) - Jannah, Muftia; Arifinsyah, Arifinsyah; Sahrin, Abu (ANWARUL, 2024)
The act of khurafat is strongly against Islamic teachings because it is not mentioned in the Al-Qur'an or the Prophet Muhammad SAW's Sunnah, yet it is nevertheless done and believed in Islamic society today. The author of this study discusses Muhammadiyah's contribution to the Islamic Society of Pegajahan District's (Case Study of Sukasari Village) 2023 victory over Khurafat. Finding out which of Khurafat's deeds are still performed and accepted by the Islamic community is the goal of this study. What part does Muhammadiyah play in helping Islamic society in Pegajahan Subdistrict, Sukasari, overcome khurafat? What are the circumstances that both encourage and hinder Muhammadiyah in doing so. This kind of field research gathers data by making direct observations of the subject of the study. This study used a qualitative, phenomenological approach to describe events that happened in the field, as gathered from interviews, documentation, and observations. The study's findings highlight Muhammadiyah's contribution to ending khurafat, a practice that is still often practiced in Islamic communities today. However, a person's faith may be harmed by this act of khurafat. In this instance, Muhammadiyah assigns the Islamic community its responsibility, claiming that khurafat is a doctrine that is against Islam and an act of disobedience that Allah SWT detests. As His slaves, we ought to practice greater piety.